(untitled) (diségno, 2026)
Constructive honesty was one of the premises of modern architecture. The best way for architects to make reality perceptible was to leave the structural elements apparent. From 1930 to the 1960s, this discussion took place in Brazil. In this way, one question emerged: What is the symbolism of a structural column in modern architecture? In the present article, we discuss the geometry of columns designed by the architect João Batista Vilanova Artigas (1915-1985) between the ’50s and ’60s. Vilanova Artigas documented his vision of architecture in his texts, which discuss the relationship between architecture, technique, and construction. We identified concepts that guided his design strategies, particularly how structure shapes architecture. Our research used drawing as a powerful tool to reveal geometrical characteristics in the constructed buildings, as well as to contribute to clarifying these concepts. Based on the original technical drawings, we modeled the structure of selected projects to investigate and reveal the constructive system, paying attention to the geometrical characteristics of the columns. The obtained results allowed us to demonstrate the sculptural character of the Vilanova Artigas columns based on the morphological analysis of the trapezoidal geometries. Furthermore, the research results reveal that Vilanova Artigas designed his architectural projects and structural conception as one thing, in an original and innovative way, harmonizing art and technique.